A Modification of Bai Bithaman Ajil Instrument through Musharakah Mutanaqisah: Fixation of Robust Optimisation into Rule 78 (Global Journal of Science Frontier Research, 2015)
The development of Islamic financial system in Malaysia had lead to various innovation and establishment of new instruments and concepts whether in debt-based financing or equitybased financing. Though several concepts have been modified to fulfill consumer's need, however, each and every one of the models should abide the law of Shariah. For over a few decades, Malaysia has been the lead country in applying the Bai Bithaman Ajil instrument in property financing. Until recently, a few legal cases have emerged and its compliancy towards Shariah has been debated among the scholars and consumers itself. In spite of the expose issues, a new proxy has been introduced. Musharakah Mutanaqisah is introduced as an equityfinancing and is proven to be conforming towards Shariah as its ownership is shared between the bank and consumer. In contemplation of making the debt-based financing compliance towards Shariah, this journal is to schemed a new model in which the original model of Bai Bithaman Ajil is embedded with profit sharing ratio exist in Musharakah Mutanaqisah.
Keywords: bai bithaman ajil; musharakah mutanaqisah; profit sharing ratio; rule 78; robust optimisation